Evaluation of Risk of Zoonotic Pathogen Transmission in a University-Based Animal Assisted Intervention (AAI) Program - Boyle, Sara F.; Corrigan, Virginia K.; Buechner-Maxwell, Virginia; Pierce, Bess J. (Frontiers in Veterinary Science, 2019)
Introduction: Previous studies have shown that apparently healthy animals participating in Animal-Assisted Interventions (AAI) have the potential to asymptomatically carry and even transmit zoonotic pathogens to people, which is of particular concern for therapy animal teams visiting healthcare settings. This two-part study was designed to investigate the risk of zoonotic pathogen transmission within a university-based AAI program as a combination of the prevalence of these pathogens in the animal population as well as the handlers' understanding of the risks of zoonoses in AAI and their adherence to infection control practices. Methods: In part one of the study, AAI program records were retrospectively reviewed and infectious disease screening test results were compiled from 22 dogs and 2 cats. Screening tests for dogs and cats included a zinc sulfate fecal float, fecal culture, and nasal and perianal skin swabs for methicillin-resistant Staphylococcus aureus (MRSA) and methicillin-resistant Staphylococcus pseudointermedius (MRSP). Additional tests for cats were blood cultures for Bartonella henselae and Toxoplasmosis IgG and IgM antibody titers. In part two, a survey was conducted of 40 registered therapy animal handlers to assess knowledge, attitudes, and perceptions regarding risk of infectious disease transmission in AAI settings, including risk to the animal, the handler, and those being visited. Results: In part one, there were 17 total positive results of the 118 infectious disease screenings performed, 14 of which were potentially zoonotic organisms. In part two of the study, a majority (70%) of respondents expressed they had no concerns regarding infectious disease transmission in AAI settings. Despite handler education and guidelines, adherence to infection control practices was lacking. Discussion: The results of this study support prior findings that animals participating in AAI can be asymptomatic carriers of zoonotic organisms. Compliance with infection control practices and hand hygiene are paramount to mitigate risk of zoonotic disease transmission, but was inconsistent among this group of handlers. Given the popularity of AAI programs in the U.S., similar studies should be performed on a larger scale to determine the level of adherence to currently recommended practices and potential need for improvement in infectious disease control education and/or policies.